Proposed Packaging of Assar Fish Products with Methods Quality Function Deployment - Tamrin Tajuddin; Irman Amri; Syach Reza Syamsuddin; Asih Ahistasari (PT. SAFARI AMALIA, 2022)
Generally, selling fish asar by the community, the seller only wraps or packs fish asar in the traditional way, using banana leaves. Traditional asar fish packaging is still carried out in the Sorong city area, especially in the market and its surroundings. So action or change is needed so that the asar fish which is the interest of the residents of the city of Sorong is still protected by the cleanliness and quality of the asar fish product. The packaging used to pack asar fish products is Polypropylene (PP) plastic packaging. The choice of packaging with this material is because it is strong, resistant to chemicals, heat, oil, transparent, and flexible. Quality Function Deployment is a product development system that starts from product design, manufacturing processes until the product is in the hands of consumers, where product development is based on consumer desires. This study aims to produce packaging designs for asar fish products that meet consumer desires using the Quality Function Deployment method. The research begins with distributing questionnaires, identifying consumer desires, determining the value of importance rating, technical response, technical correlation matrix, relation matrix, planning matrix, determining target specifications, making House of Quality. The resulting packaging design is a rectangle measuring 35 cm x 18 cm, made of Polypropylene (PP) plastic, packaging using a sticker measuring 12 cm x 12 cm, and the packaging is pressed using a sealer.